Fluid Flow-Based Vibration Energy Harvesters: A Critical Review of State-of-the-Art Technologies - Sadia Bakhtiar; Farid Ullah Khan; Hailing Fu; Amal Z. Hajjaj; Stephanos Theodossiades (Applied Sciences)
Energy harvesting technology plays an important role in converting ambient energy into useful electrical energy to power wireless sensing and system monitoring, especially for systems operating in isolated, abandoned or embedded locations where battery replacement or recharging is not a feasible solution. This paper provides an integrative study of the methodologies and technologies of energy harvesting from fluid flow-induced vibration (FIV). The recent research endeavors contributing to flow-based energy harvesting have been reviewed to present the state-of-the-art issues and challenges. Several mechanisms on FIVs including vortex-induced vibrations (VIVs), flutter, galloping and wake galloping are thoroughly discussed in terms of device architecture, operating principles, energy transduction, voltage production and power generation. Additionally, advantages and disadvantages of each FIV energy harvesting mechanism are also talked about. Power enhancement methods, such as induced nonlinearities, optimized harvester’s configuration, hybridization and coupling of aerodynamic instabilities, for boosting the harvester’s output are also elucidated and categorized. Moreover, rotary wind energy harvesters are reviewed and discussed. Finally, the challenges and potential directions related to the flow-based energy harvesters (FBEHs) are also mentioned to provide an insight to researchers on the development of sustainable energy solutions for remote wireless sensing and monitoring systems.